Celiac Disease and Non-celiac Wheat Sensitivity: State of Art of Non-dietary Therapies - Serena, Gloria; D'Avino, Paolo; Fasano, Alessio (Frontiers in Nutrition, 2020)
Gluten related disorders (GRD), which include celiac disease, non-celiac wheat sensitivity and wheat allergy are heterogeneous conditions triggered by ingestion of gluten-containing grains. Together, their prevalence is estimated to be 5% in the general population, however, in the last years the number of diagnoses has been rapidly increasing. To this day, the gold standard treatment for these disorders is the complete removal of gluten-containing grains from the diet. Although this therapy results effective in the majority of patients, up to 30% of individuals affected by GRD continue to present persistent symptoms. In addition, gluten-free diet has been shown to have poor nutritional quality and to cause a socio-economic burden in patients' quality of life. In order to respond to these issues, the scientific community has been focusing on finding additional and adjuvant non-dietary therapies. In this review, we focus on two main gluten related disorders, celiac disease and non-celiac wheat sensitivity. We delineate the actual knowledge about potential treatments and their relative efficacy in pre-clinical and clinical trials.